Development of an Environmental Character Education Model for Student Character Through Ecological Schools in Elementary Schools (Case Study of Ecological Schools in Purwakarta District) - Syarif Hendriana; Kama Abdul Hakam; Sofyan Iskandar; Momod Abdul Somad (Jurnal Penelitian Pendidikan IPA, 2025)
The development of the Environmental Character Education Model is the extent to which character education, pro-environmental behavior, environmental character and school culture affect the character of students in elementary schools in Purwakarta district both individually and through ecological schools. This study aims to determine and analyze the effect of developing an environmental character education model on student character both individually and through ecological schools. The research method used is a case study with a quantitative approach to ecological schools in Purwakarta Regency with statistical tools using SEM with the Smart PLS test tool and the Sobel test. The results showed that there is an influence of Character Education, Pro-Environmental Behavior, Environmental Character and School Culture on Ecological Schools and Impact on Student Character in Ecological Elementary Schools in Purwakarta Regency.